Confronting and Deferent as Co-Referential Markers in English and Arabic with Special Reference to the Glorious Quran Texts - Khalil, Omar Abd AlAziz; Abed, Ammar Abd AlWahab (Al-Adab Journal, 2022)
Confronting and deferent, as linguistic devices, have important functions in deciding the meaning of a text. Sentences in any language are structured according to particular criteria defined by grammarians. The probable variations in word order resulting from of confronting or deferring specific sentence components may be problematic for both language users and learners of English and Arabic. Thus, the present study basically aims to identify the main processes of confronting and deferent in both English and Arabic, to identify sentence patterns in which confronting and deferent take place, and to identify sentence components involved in confronting and deferent in both English and Arabic. All these topics are discussed with reference to the Glorious Quran. To this end, Palmer (1981), Qurik et al. (1985), Al Museeri (2005), and Hammami et al. (2008) have been adopted to analyze the data in a qualitative method. The study revealed that confronting and deferent are just two of various strategies used to achieve variety in communication and expression. Although there are numerous variations between the two languages in this respect, they also have some similarities. Among these similarities is that both languages involve the shifting of components into beginning or final position to achieve specific goals such as emphasis, suspense, etc. There are many types of confronting and deferent processes in the two languages based on sentence components and sentence patterns involved in confronting and deferent. The components that can be involved in confronting and deferent in the two languages are the subject and predicate, subject and object, adverbs, pronouns, and several other elements. These confronting and deferent cases are found in nominal, verbal, prepositional phrases, and adjective phrases. This study is a call for EFL learners, EFL teachers, and those who are concerned with linguistic research and textbook writing to take into consideration the strategies used in different text types to achieve various communicative goals.